Do consumers want to control their personal data? Empirical evidence. Issue 110 (February 2018) - Prince, Christine
Highlights: An overview of individuals' privacy empowerment is provided. Concerns over information privacy explain online users' need for control over their personal information flows. The effects of willingness to disclose personal information on web users' predisposition to use privacy controls vary according to information type. Compensation is a factor to motivate online users to use privacy controls over data flows. Abstract: The rise of new technologies has brought new challenges regarding the protection of personal data, as a vast amount of personal information is being published and shared. Because personal data are extremely valuable for many digital businesses, it is crucial to understand to what extent individuals want to exert control over the disclosure of their personal data. This paper aims to assess the factors that affect web users' predisposition to exert control over personal data flows, using a dataset collected in France in 2014 that targets online users and their privacy. Our results demonstrate that those who are more likely to disclose personal data express a greater propensity to use privacy controls. Additionally, our research results show that online users' propensity to use privacy controls is likely to be driven by the type of personal information they are willing to share. Furthermore, our findings show clearly that compensation is a factor to motivate online users in using privacy controls over data flows.